Pathways of service user participation in mental health decision-making in Lebanon - Thurayya Zreik; Sandy Chaar; Michelle Lokot; Rozane El Masri; Rayane Ali; Bassel Mekssasi; Joseph Elias; Michele Asmar; Martin McKee; Felicity L. Brown; Rabih El Chammay; Bayard Roberts (SSM - Mental Health, 2025)
Inclusive participation of mental health service users is critical for effective decision-making and governance, yet remains underexplored in humanitarian settings. Lebanon, facing protracted crises and hosting over 1.5 million Syrian refugees, provides a unique case to examine pathways of service user participation in mental health decision-making. This qualitative study investigates barriers, facilitators, and power dynamics influencing service user participation at the micro-, meso- (service), and macro- (policy) levels. Semi-structured interviews and focus group discussions were conducted with 33 purposively selected participants, including Syrian and Lebanese service users, NGO staff, and UN representatives. Data were collaboratively analysed using Dedoose software based on codes developed deductively and inductively. Our findings reveal that participation is limited and predominantly consultative, with power imbalances including gender, socioeconomic status, stigma, and displacement status creating significant barriers. Users reported decision-making power at the individual level, particularly in seeking services and treatment planning, but meaningful participation at service or governance levels was rare. Providers highlighted efforts to gather user input but often framed participation as part of routine monitoring and evaluation. Reluctance to engage formal governance structures, due to mistrust and structural and attitudinal barriers, further inhibited participation. Strategies to enhance meaningful participation include increasing awareness, capacity-building, promoting flexibility in service design, and strengthening user-led advocacy. Addressing power imbalances and promoting inclusive, user-centered approaches are essential to advancing inclusion in mental health systems, with valuable implications for humanitarian and crisis-affected settings globally.